Macroeconomic perspective on global imbalances. - Lee, Pei Hua. (2010)
The recent global financial crisis has been described as the abrupt unwinding of the macroeconomic imbalances that have emerged over the last decade. The global imbalances, with rising current account deficits in the United States and massive surpluses in Asia and oil-exporting countries, have been viewed as a threat to global economic and financial stability. This paper outlines the economic forces behind the global imbalances, and focuses on the theoretical approaches to the current account and their implications on the external and internal adjustment process. Using an autoregressive distributed-lag model within an error correction framework, this paper investigates the fundamental causes and proximate determinants of the US current account. Econometric results show that in the long run, the US current account position is negatively correlated with the real exchange rate and domestic GDP, and positively correlated with world GDP, as postulated by the elasticity approach. In addition, US household savings are shown to contribute significantly to the deficit, while corporate savings and government budget balance do not. Overall, the empirical results substantiate our argument that both internal and external adjustments are required to rebalance the global economy, starting with closing the US external deficit.